A Descriptive Comparative Study of Marital Satisfaction among Healthy Women and Women with Breast Cancer - Razieh Hayati; Shahnaz Torkzahrani; Sedigheh Amir ali akbari; Elham Faghihzadeh (Mashhad University of Medical Sciences, 2022)
Background & aim: Breast cancer, the most common malignancy among women, affects many aspects of their lives. The present study was conducted to compare marital satisfaction in women with breast cancer and healthy women.Methods: This descriptive comparative study was performed on 95 women with a definitive diagnosis of breast cancer and 95 healthy women who referred to the health centers and breast cancer clinics of Mostafa Hospital in Ilam, Western Iran in 2019.  Data were collected using demographic and Enrich Marital Satisfaction Questionnaires. Data analysis was carried out by SPSS software (version 20) using independent t-test and Chi-square test.Results: The mean total score of marital satisfaction in the healthy group was higher than breast cancer group (125.41± 10.17 vs 96.27 ± 9.46) (P˂0.001). The mean score of marital satisfaction dimensions including marital satisfaction (38.65± 4.70 vs 27.11± 4.16); communication (35.10 ±5.59, vs 28.91 ±6.41); conflict resolution (30.54 ±6.45, vs 25.74 ± 5.90) and ideal distortion (21.12 ±3.36 vs14.51 ± 2.79) was also higher in the healthy group compared with breast cancer group (P˂0.001).Conclusion: Breast cancer can result in reduced marital satisfaction in different dimensions. Therefore, providing appropriate psychological counselling help women with cancer and their spouses to enhance their marital satisfaction.